Oryctolagus cuniculus - Robert S. Hoffmann (Smithsonian Institution Press, 1993)
Oryctolagus cuniculus (Linnaeus, 1758). Syst. Nat., 10th ed., 1:58. TYPE LOCALITY: "in Europa australis" [= Germany]. DISTRIBUTION: W and S Europe through the Mediterranean region to Morocco and N Algeria; original range probably limited to Iberia and perhaps NW Africa; introduced on all continents except Antarctica and Asia; see Gibb (1990). Worldwide as domesticated forms. STATUS: The form huxleyi of the Atlantic and Mediterranean isls "may be endangered" (Gibb, 1990). SYNONYMS: algirus (Loche, 1858); borkumensis Harrison, 1952; brachyotus Trouessart, 1917; campestris (Meyer, 1790); cnossius Bate, 1906; fodiens Gray, 1867; habetensis Cabrera, 1923; huxleyi Haeckel, 1874; kreyenbergi Honigmann, 1913; nigripes Bartlett, 1857; oreas Cabrera, 1922; vermicula Gray, 1843; vernicularis Thompson, 1837. COMMENTS: The specific name is probably based on a feral specimen (Gibb, 1990). Published as part of Robert S. Hoffmann, 1993, Order Lagomorpha, pp. 807-827 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 822, DOI: 10.5281/zenodo.7353088